Sustainable financing for mental health and noncommunicable diseases: what’s at stake? - Dan Chisholm; David Watkins; Jumana Qamruddin (BJPsych Open)
Informed by an international dialogue on sustainable financing for noncommunicable diseases and mental health in 2024, this Editorial explores some of the key financing issues to be addressed in September 2025 at the United Nations General Assembly high-level meeting on noncommunicable diseases and mental health, including those relating to domestic resource mobilisation, external assistance and health financing reforms.